Engaged Palaeoethnobotany on the Northern Plains: A Compelling Future for Medicinal Plant Research - Stuart, Glenn S. L.; Coward, Eryn L. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
The University of Saskatchewan Department of Archaeology & Anthropology became the first academic Department in Canada to publicly offer a Statement on Reconciliation. Most archaeologists recognize our colonial past and agree we need to expand our focus to incorporate better the thoughts, actions, and desires of the descendant communities of those who produced the material and nonmaterial remains we study. As a subdiscipline of archaeology, palaeoethnobotany with its emphasis on traditional plant use is well-positioned to engage fully with descendant communities. The Northern Plains would seem an ideal candidate for such research, given the rarity of existing palaeoethnobotanical research and the apparent absence of engaged research on medicinal plants. Current literature on the Northern Plains does include various ethnobotanical accounts, including discussion of plants with medicinal purposes. Though rare, there are also a few palaeoethnobotanical studies, which typically incorporate ethnobotanical data to aid interpretations. But what is lacking are clear attempts to bridge these sources of information; to conduct studies specifically designed through the coordinated efforts of Indigenous Knowledge Keepers and Healers with palaeoethnobotanists. We discuss how community-engaged scholarship of medicinal plants research on the Northern Plains may benefit both palaeoethnobotany and descendant communities.